SHORT-TERM CORROSION RESPONSE OF METALS IN LIME MORTAR - Pavla Bauerová; Zdeněk Prošek; Jitka Krejsová; Martin Keppert (Acta Polytechnica CTU Proceedings, 2019)
Even though the corrosion of steel in concrete is very well described, the corrosion processes in lime environment studied very rarely. This environment is obviously also basic and its pH decreases in time, but the obtained results indicate important differences in behaviour of these two systems. Corrosion response of carbon steel, zinc platted steel, copper, brass and lead placed in lime mortar was studied by help of SEM microscopy.